Swirling flow at vertical shaft spillways with circular piano-key inlets. Issue 2 (4th March 2017) - Shemshi, Roya; Kabiri-Samani, Abdorreza
ABSTRACT: Swirling flow at vertical shaft spillways with an innovative geometry, circular piano-key (CPK) inlet, is investigated based on model experimentation. Detailed measurements of head–discharge relationships, threshold submergence, and flow hydraulic characteristics were performed for CPK spillways. Conditions at the beginning of the submergence are analysed, because this situation is related to a condition in which flow instabilities appear on the spillway crest. The results show that the swirling flow strength for flow through the CPK spillway is several times lower than that for simple shaft spillways. This structure yields excellent hydraulic performance, e.g. increasing the weir overflow length by at least 200% without changing the global size of the shaft spillway, thereby increasing the flow discharge up to six times compared with a simple shaft spillway. Finally, two correlations are derived for determining the threshold submergence depth and discharge coefficient of CPK spillways.